ANALYSIS OF OBSTACLES TO ANJAB & ABK NEEDS PLAN AT MEDAN CITY HEALTH OFFICE - Hasibuan, Rapotan; Dalimunthe, Ulfa Fadilla; Siregar, Oktavia Sukmayati; Azzahra, Dea (HEARTY, 2024)
Health human resources (SDMK) are indispensable in improving the degree of public health in a country. The determination of human resource needs is carried out using the Anjab & ABK needs plan (Position Analysis and Workload Analysis). However, in its implementation, several obstacles hinder the effectiveness of the Anjab & ABK needs assessment at the Medan City Health Office. The purpose of the study was to analyze SWOT on the RENBUT ANJAB & ABK Barriers in the Medan city health office. The type of research used in this study is descriptive research using a qualitative approach. This research uses a case study design. Data collection techniques in this study were carried out by observation and in-depth interviews. The subjects of the study were selected purposively. The key informants in this study were the head of the Head of Health Human Resources, the Needs Plan Program Holder at the Medan City Health Office, 2 Health Workers, and 2 Communities. The data is then analyzed narratively to elaborate the discussion and conclusions. The results showed that the obstacles in RENBUT ANJAB   & ABK in the Medan City Health Office were in Needs Planning In the Medan City Health office, the obstacle that existed was the lack of a team in preparing the plan, causing officers holding the renbut program to be overwhelmed in inputting additional data. Pegwai agencies become obstacles in inputting RENBUT data due to a lack of sensitivity in inputting scheduled data so that data results are more skewed in wants rather than needs. Irregular employee mutations also cause data to be inappropriate so that the agency will experience worker vacancies.